The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12909-019-1477-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of empathy and psychological need satisfaction in pharmacy students’ burnout and well-being

Abstract: BackgroundThe purpose of this study was to examine the relationship between Korean pharmacy students’ empathy and psychological need satisfaction and their levels of burnout and psychological well-being, using structural equation modeling.MethodsThe participants were 452 pharmacy students from five South Korean universities. The Jefferson Scale of Empathy (Health Professions Students version), the Activity-Feeling States Scale, and the Maslach Burnout Inventory-Student Survey were used to assess empathy, psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 92 publications
1
42
0
Order By: Relevance
“…Female doctors' emotion is more influenced by the doctor-patient relationship. Previous studies have shown that female doctors tend to show more empathy (Gleichgerrcht and Decety, 2013;Cho and Jeon, 2019) and offer patients more comfort and emotional care. In addition to the increased demands of work, family responsibilities and dissatisfaction with work-life balance also play an important role in the mood of female doctors (Beckett et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female doctors' emotion is more influenced by the doctor-patient relationship. Previous studies have shown that female doctors tend to show more empathy (Gleichgerrcht and Decety, 2013;Cho and Jeon, 2019) and offer patients more comfort and emotional care. In addition to the increased demands of work, family responsibilities and dissatisfaction with work-life balance also play an important role in the mood of female doctors (Beckett et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Their work is not only related to life and death but also to a patients' family happiness and even to a healthy and stable society. Previous studies have shown that women physicians tend to display more empathy and report especially high empathic concern for patients (Gleichgerrcht and Decety, 2013;Cho and Jeon, 2019). Moreover, women are more likely than male physicians to counsel their patients and spend more time with each patient (Barnett et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Life satisfaction, as a concept concerning the cognitive aspect of subjective wellbeing, is defined as an individual’s conscious evaluation of his or her life based on self-set standards [19]. The research conducted among 452 pharmacy students from five South Korean universities using structural equation modelling (SEM) found that exhaustion and cynicism, which are two facets of the Maslach Burnout Inventory—Student Survey (MBI-SS), were both significantly negatively correlated with life satisfaction [20]. A three-wave seven-year prospective study among 3255 Finnish dentists revealed that burnout predicted depressive symptoms and lowered life satisfaction [21].…”
Section: Introductionmentioning
confidence: 99%
“…The following values were considered to indicate a fair fit: CMIN/d.f. <3, NFI >0.9, IFI >0.9, CFI >0.9 and RMSEA <0.08 . Composite reliability was also calculated for each subscale …”
Section: Methodsmentioning
confidence: 99%